Can youth save Malaysia's democracy? - Weiss, Meredith L. (Nanyang Technological University, 2023)
In 2019, Malaysia passed a bipartisan constitutional amendment that lowered the country’s voting age from 21 to 18, setting in train a dramatic expansion of the electorate and downward tilt in the median voter age. Malaysian youth are, on average, both fairly well informed and politically aware, and concerned about their country’s direction and their own prospects. Yet we should not expect that a sudden flood of young voters will upend Malaysia’s next elections. Like their elders, not all youth share the same priorities or are committed to a similar democratic vision. Especially key are differing perspectives on the role of race and religion in government, and on the ethno-nationalist coalition that came to power in early 2020, supplanting the reformist coalition elected in 2018. Nevertheless, elections are not the only way youth can make their mark on Malaysian democracy. Today’s youth came of age in an era of expanded avenues for awareness-raising and mobilisation. Regardless of personal ideological or policy preferences, Malaysian youth are thus more likely acculturated to new ways of approaching and engaging in politics, positioning them to develop and model new habits of participation and enforcing accountability — habits conducive to more robust, if incremental, liberalisation.